A Critical Look at the Bigger Picture: Macro-Level Discourses of Language and Technology in the United States. (25th August 2018) - Hellmich, Emily
Abstract : Despite its numerous benefits and potentialities for language learning and teaching, digital technology can also play a role in creating and maintaining inequality (Kern, 2014; Selwyn, 2013). While critical CALL often focuses on micro-level issues and contexts, macro-level perspectives, including discourses, are also essential to consider (Helm, 2015): From ecological and language-as-discourse perspectives, macro-level discourses have the potential to impact and shape CALL practices and contexts (Blin, 2016; Blommaert, 2005). Using critical discourse analysis methods (Blommaert, 2005; Fairclough, 2001), this article takes the 2017 American Academy of Arts and Sciences (AAAS) report, "America's Languages: Investing in Language Education for the 21st Century, " as a window into macro-level discourses of language and technology in American society today. Findings reveal a series of interrelated frames and scales that, taken together, suggest a neoliberal discourse that positioned language, technology, and ultimately CALL as tools to enhance national competitiveness on a global marketplace. The article concludes with implications of these findings for the CALL field.